The Development of Typologies, Design Patterns and Scaled Models Bio-Inspired by Mangrove Species - Sayuti et al., Nurul ‘Ayn Ahmad (International Journal of Advanced Science and Technology, 2019)
Mangrove is unique type of plants with distinctive roots that inhabit rivers or beaches. It is estimated that more than 36 species of mangroves have been identified in Sungai Merbok, Kedah, Malaysia alone and it is considered to be one of the largest collections of mangrove species in the world. Analogy is a process where the ideas are depicted or illustrated from a subject matter is a common process for designers and artists whom using nature as source of inspirations. Every part of the plant shown a different variation of roots, fruits, flowers, leaves and other physical parts according to the species or family name. The aim of this study is to observe, identify, and translate the common physical forms of the mangroves into series of patterns and to record the findings on the preferences of the potential consumers towards the scaled models developed. This study can be divided into two phases and it is estimated that 265 basic design patterns were sketched and developed in the first phase. Then the design patterns where chosen to be developed as 4 scaled models and it was showcased publicly in the art exhibition. To find out more on the preferences of potential consumers, a survey was performed for three months. About 494 responses received and the findings were analysed and discuss on which scaled models is preferred the most. This study is also done to explore potential of mangroves to be developed further in different forms of design, especially in industrial design field.